Public debt and borrowing: Are governments disciplined by financial markets? - Nicolas Afflatet (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
With the announcement to intervene on the financial markets in case of need to keep the Eurozone intact, the ECB has attenuated the pressure of the markets on the endangered peripheral countries of the Eurozone. Critics argue that by eliminating the market's disciplining interest mechanism, governments in the crisis countries will not carry out reforms and consolidate their budgets. Based on data for the European Union, 2SLS models are tested to investigate if governments react to rising interest rates or deteriorating borrowing conditions. The results are threefold: First, governments do react to rising bond yields on the secondary market by raising their primary surpluses. Second, they also do so when they feel the rising interest rates in their budgets. Third, governments react to changing borrowing conditions but contrary to the expected direction. In case of deteriorating conditions they lower primary surpluses. This is a result of the dominating influence of falling growth rates. These differentiated findings show that the market discipline mechanism only works to a certain extent. For most countries market forces did not suffice to reach sustainable public debt situations. To restore the no-bail-out-rule could be another disciplining mechanism to reach financial sustainability.
Keywords: H60; 330; Market Discipline Hypothesis; Public Deficits; Public Debt; Sovereign Bond Yields; Eurozone; Public Debt Crisis